Endovascular Treatment of Ischemic Stroke: An Updated Meta-Analysis of Efficacy and Safety. (May 2017) - Vidale, Simone; Agostoni, Elio
Background: Recent randomized trials demonstrated the superiority of the mechanical thrombectomy over the best medical treatment in patients with acute ischemic stroke due to an occlusion of arteries of proximal anterior circulation. In this updated meta-analysis, we aimed to summarize the total clinical effects of the treatment, including the last trials. Methods: We performed literature search of Randomized Crontrolled Trials (RCTs) published between 2010 and October 2016, comparing endovenous thrombolysis plus mechanical thrombectomy (intervention group) with best medical care alone (control group). We identified 8 trials. Primary outcomes were reduced disability at 90 days from the event and symptomatic intracranial hemorrhage. Statistical analysis was performed pooling data into the 2 groups, evaluating outcome heterogeneity. The Mantel-Haenszel method was used to calculate odds ratios (ORs). Results: We analyzed data for 1845 patients (interventional group: 911; control group: 934). Mechanical thrombectomy contributed to a significant reduction in disability rate compared to the best medical treatment alone (OR: 2.087; 95% confidence interval [CI]: 1.718-2.535; P < .001). We calculated that for every 100 treated patients, 16 more participants have a good outcome as a result of mechanical treatment. No significant differences between groups were observed concerning the occurrence of symptomatic hemorrhage (OR: 1.021; 95% CI: 0.641-1.629; P = .739). Conclusion: Mechanical thrombectomy contributes to significantly increase the functional benefit of endovenous thrombolysis in patients with acute ischemic stroke caused by arterial occlusion of proximal anterior circulation, without reduction in safety. These findings are relevant for the optimization of the acute stroke management, including the implementation of networks between stroke centers.